Beyond City Image: Affective Drivers of Student Relationships in a Metropolitan Education Context - Yudhiet Fajar Dewantara; Michael Christian; Eko Retno Indriyarti (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2026)
This study aims to examine how Generation Z students perceive Jakarta as an urban education city and how these perceptions influence students’ relationship outcomes. The research is grounded in the growing competition among education cities and the shifting ways students interpret cities as academic, social, and identity-forming ecosystems. A quantitative survey method was employed, involving Generation Z students studying in Jakarta, with constructs including city image, city attributes, city love, and university city brand personality. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that emotional attachment to the city and the personality of the city as an educational brand play a more decisive role in shaping student satisfaction, loyalty, and recommendation intentions than cognitive city image and functional urban attributes. These results suggest that in a complex metropolitan context such as Jakarta, affective and symbolic factors serve as key differentiators in strengthening student–city–university relationships. This study contributes to the literature on city branding and higher education marketing and offers practical insights for universities and city policymakers in developing education city strategies that resonate with Generation Z students.